SENSITIVITY OF APPLE MANGO LEAVES (Mangifera indica) SOLUTION TOWARD Edwardsiella tarda - Yosri Yosri; Henni Syawal; Morina Riauwaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research was conducted from Juni to September 2018, atParasites and Fish Disease Laboratory, Faculty of Fisheries and Marine, University of Riau. The Purpose of this study was to determine the sensitivity of apple mango leaves (Mangifera indica) solution as antimicrobial to Edwardsiella tarda, the range of Minimal Inhibitory Concentration (MIC) and the lethal dose (LD50) of apple mango leaves (Mangifera indica) solution against to (Pangasiussp.) with length 8-10 cm by immersion for 24 hours. Sensitivity test is using the method of Kirby-Bauer disk blank 6 mm disc with dose used were 100%, 90%, 80% , 70%, 60%, 50%, 40%, 30%, 20%, 10%,9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1% and control Tetracyclin. The result shown that the apple mango leaves solution can inhibit the growth of bacteria Edwardsiella tardathat in the dose of 1% with 6,05 mm clear zone . MIC test showed this resueld is 2% has a number of colonies of bacteria aqual 282.33 CFU/mL is able to inhibit the growth of bacteria Edwardsiella tarda. Dose LD50apple mango leaves solution against catfish by immersion for 24 hours in 2% .Keywords: Apple Mango Leaves, Sensitivity, Minimum Inhibitory Concentration